A comparative modelling study of new robust packaging technology 1mm2 VCSEL packages and their mechanical stress properties - Khairul, Mohd Arshad; Muhamad, Mat Noor; Asrulnizam, Abd Manaf; Kawarada, Hiroshi; Falina, Shaili; Mohd, Syamsul (MDPI AG, 2022)
Face recognition is one of the most sophisticated disciplines of biometric systems. The use of VCSEL in automotive applications is one of the most recent advances. The existing VCSEL package with a diffuser on top of a lens intended for automotive applications could not satisfy the criteria of the automotive TS16949: 2009 specification because the package was harmed and developed a lens fracture during 100 thermal cycle tests. In order to complete a cycle, the temperature rises from −40 °C to 150 °C and then rises again from 150 °C to 260 °C. The package then needs to be tested 500 times to ensure it fits the requirements without failing in terms of appearance or functionality. To this extent, the goal of this research is to develop packaging for 1 mm2 VCSEL chips with a diffuser on top that prevents fractures or damage to the package during heat cycle testing with multiple materials. The package was created using the applications SolidWorks 2017 and AutoCAD Mechanical 2017. The ANSYS Mechanical Structural FEA Analysis program simulated all packages for mechanical stress to guarantee that all packages generated were resilient to high temperature conditions. All packages exhibit no abnormalities and are robust for various temperatures ranging from low to high. Therefore, these packaged 1 mm2 VCSEL chips with a diffuser on top provide an effective approach for the application of VCSEL suitable in high temperature conditions.